The Application of Corticosteroids in COVID-19: A Two-edged Sword - Li, Na (J Transl Int Med, 2020)
COVID-19 has become a global pandemic and requires the whole world to respond together. There is no specific antiviral treatment recommended at present for COVID-19. The patients must receive the supportive care to help relieve the symptoms and ensure appropriate infection control. Whether or not to use corticosteroids clinically caused controversy. This article has summarized previous researches about the using of corticosteroids in other viral pneumonia, related clinical data in COVID-19, and recommendations in Chinese guideline.